FTA Highlight No.6 – Wild Meat - Nasi, R.; Fa, J.E.; Vliet, N. van; Coad, L.M.; Pinedo Vasquez, M.; Swamy, V.; Tien, M.L. (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
The meat of wild animals is a crucial part of the diets of millions of families in the tropics and subtropics. It is often the most accessible and sustainable source of protein and micronutrients and can also be a significant source of revenue for many people. Enabling these people, mostly the poor, to continue consuming wildlife in a sustainable manner — while reducing the impacts of overhunting on animal populations — are the main challenges facing researchers and policymakers. Since 2011, the research and policy initiatives led by the Bushmeat Research Initiative (the BRI-CIFOR team), in conjunction with many partners and collaborators worldwide, have made substantial contributions to this topic. These efforts increase the understanding of the current levels and trends of wild meat extraction and of the importance of this wild meat to consumers. The BRI-CIFOR team has generated important new data of wild meat use across a diverse number of environments worldwide. This publication presents some of the key FTA outputs on wild meat; over the last decade these efforts have contributed to inform science, policy and practice.